Counseling on Drugs and HIV AIDS in Handling Mental Health Disorders at SMPN 33 and SMPN 34, Bulukumba Regency - Dewi, Laela Alfionita; Rachmat, Muhammad; Nasrah, Nasrah; Hidayat, Muliati; Astriana, Tiara; Yunus, Ariyati; Riskiyani, Shanti (Yayasan Mestika Nusantara Satu, 2024)
One of the most important things for humans is mental health. Based on the results of several studies, it is stated that mental health can be disrupted due to drug abuse and HIV AIDS. Adolescents are an age group that is prone to risky behavior for their mental health. Objective: participants are expected to have good awareness and knowledge related to the impact of drug abuse and HIV AIDS on mental health disorders. Method: This activity uses lecture and discussion methods. The target number is 60 people who are students at SMPN 33 and SMPN 34 in Bulukumba Regency. Result: As for the Asymp.Sig value. (2-tailed) <0.05 means that there is a difference between the pre-test and post-test values, so it can be concluded that mental health counseling influences knowledge related to drugs and HIV/AIDS in preventing mental health disorders. Conclusion: counseling can increase target knowledge about drugs and HIV/AIDS in preventing mental health disorders.